An overview study on the educational psychological assessment by measuring students' stress levels - Kosherbayeva, A. N.; Issaliyeva, S.; Begimbetova, G. A.; Kassymova, Dr. Gulzhaina K.; Kosherbayev, R.; Kalimoldayeva, A. K. (Jurnal Cakrawala Pendidikan, 2024)
This article reviews the literature on the field of bibliographic analysis of the literature on educational assessment, psychological stress during the examination period, human memory, stress in the classroom, psychometric tools, and measurement scales for students' stress. It examined the link between students' social and psychological health, stress levels, and preferred social support systems. The research subjects were Abai Kazakh National Pedagogical University first-year students (n=299) who completed the Perceived Stress Scale and a Likert rating-type scale via a Google form. The validity and reliability of the scale were respectively confirmed through "˜high' Aiken's V and Cronbach's Alpha coefficients. Structural equation modeling (SEM) analysis showed a satisfactory fit for the model. The average relationship (r=0.39) was found between stress levels and preferred social support, while a positive correlation (r=0.29) existed between preferred social support and socio-psychological health. However, the Stress Level variable only correlated with Socio-psychological Health through Preferred Social Support. The subjects preferred the University Staff and Academic advisors as social support providers over their parents. Overall, the findings indicate that higher levels of support were associated with reduced stress and improved socio-psychological health among Abai Kazakh National Pedagogical University students. Conversely, lower support levels correlated with increased stress and negative impacts on well-being.